VENTURE CAPITAL INVESTMENTS IN TECH STARTUPS- AN OVERVIEW - Rafee, B. Mahammad; Mohideen, A.J.Haja; Khatoon, Sogra; Zaheed, S.Mohammed (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Venture capital funding in India surged 50.4% year over year to $8.3 billion in the first three quarters of 2024. This resulted from an increase in transactions for above $100 million each in VC investments in Indian startups declined considerably, totalling more over $8 billion as opposed to more than $18 billion in 2022. Additionally, there were 472 agreements in 2023 compared to 815 in 2022. Seed stage, early stage, and later stage are the three segments of the Indian venture capital sector. Accel and Sequoia Capital are prominent participants in the market in 2024. According to research by Global Data, venture capital (VC) spending in India surged 50.4% year over year to $8.3 billion in the first three quarters of 2024. The jump was ascribed by the data analytics and consultancy organisation to a boost in transactions valued above $100 million each. Between January and September 2024, 883 deals were announced, reflecting a 7.3% increase in volume over the same period in 2023. Between 2023 and 2024, the stated value of these transactions climbed from $5.5 billion to $8.3 billion. According to GlobalData, the growth was boosted by high-value transactions, such as $665 million and $340 million raised by Zepto in two different investment rounds, $300 million by Meesho, $216 million by PharmEasy, and $210 million by PhysicsWallah. The present study is to explore the Venture capital in Tech startups in India.